Surface soil temperature across an experimental burn severity gradient in far northeastern Siberia, 2013-2017 - Heather D. Alexander (Arctic Data Center, 2018)
Fire severity is increasing across the boreal forest biome as climate warms, and initial post-fire impacts on tree demographic processes could be an important determinant of long-term forest structure and carbon dynamics. To examine soil burn severity impacts on tree regeneration and soil conditions, we conducted experimental burns in summer 2012 that created a gradient of residual post-fire soil organic layer (SOL) depth within a mature, sparse-canopy Cajander larch (Larix cajanderi Mayr.) forest in the Eastern Siberian Arctic. During subsequent growing seasons from 2013 to 2017, we measured surface (~ 5-cm depth) soil temperature across the severity gradient.